Lipid-encapsulated gold nanoparticles: an advanced strategy for attenuating the inflammatory response in SARS-CoV-2 infection - Sanjeevram Dhandapani; Yujeong Ha; Rongbo Wang; Tae Woo Kwon; Ik-Hyun Cho; Yeon-Ju Kim (Journal of Nanobiotechnology)
Abstract Background Nanodrugs play a crucial role in biomedical applications by enhancing drug delivery. To address safety and toxicity concerns associated with nanoparticles, lipid-nanocarrier-based drug delivery systems have emerged as a promising approach for developing next-generation smart nanomedicines. Ginseng has traditionally been used for various therapeutic purposes, including antiviral activity. This study aimed to prepare a biocompatible and therapeutically potent Korean ginseng nanoemulsion (KGS-NE) using ginseng seed oil (GSO), optimize its encapsulation and drug delivery efficiency, and evaluate its antiviral activity. Results Various techniques were utilized to confirm the KGS-NE formation. Energy-dispersive X-ray spectroscopy identified gold nanoparticles with the highest Au peak at 2.1 keV. Selected area diffraction patterns revealed crystallographic structures. FT-IR spectrometry detected functional groups, with peaks at 2922.09 cm−1 (alkene C–H stretching), 1740.24 cm−1 (aldehyde C=O stretching), and 1098.07 cm−1 (C–O stretching in secondary alcohol). Storage stability studies showed that KGS-NE maintained its size and stability for 6 months at 4 °C. The KGS-NE exhibited a dose-dependent suppression of HCoV-OC43 viral replication in Vero E6 cells. RNA sequencing analysis unveiled differentially expressed genes (DEGs) specifically involved in the ABC transporters signaling pathway. KGS-NE oral administration facilitated the recovery of mice induced with the receptor binding domain (RBD) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein, as confirmed by inflammatory markers expression in lung tissue. In the Syrian hamster infected with the SARS-CoV-2 model, the lungs dissected showed enlarged morphology and induced inflammatory cytokines. This effect was mitigated with KGS-NE oral administration, as observed through H&E and qRT-PCR analysis. Biochemical analysis at various oral administration concentrations demonstrated that KGS-NE had no adverse effects on the kidney and liver. Conclusions Our findings strongly suggest that oral administering KGS-NE in mice and Syrian hamster models has the potential to effectively mitigate lung inflammation against coronavirus. This indicates a promising new strategy for developing the antiviral nano-agent against SARS-CoV-2. Graphical Abstract